PENGARUH VARIASI KONSENTRASI EKOENZIM DAN GULA MERAH PADA PERTUMBUHAN JAMUR TIRAM PUTIH (Pleurotus ostreatus) - Fitriani Fitriani; Najla Lubis; Sri Mahareni Br. Sitepu (Fakultas Pertanian, Universitas Janabadra, 2023)
This study aims to determine the effectiveness of using different doses of eco-enzymes in the cultivation of white oyster mushrooms (Pleurotus ostreatus), knowing the effectiveness of using different doses of brown sugar in the cultivation of white oyster mushrooms . White oyster mushrooms require nutritional supplements during their growing years. Additional nutrients can be obtained using water-soluble ecoenzymes and fertilizing the substrate of white oyster mushrooms. Ecoenzyme nutrients and brown sugar can increase the yield and growth of white oyster mushrooms at harvest time. This study used factorial complete randomized design (RAL) with 2 factors, 16 treatments, 3 repeats, and 48 baglogs. G0 = 0%/baglog, G1 = 40%/baglog, G2 = 80%/baglog, G3 = 120%/baglog. Factor Pertreatment 2 Using eco enzyme with symbol